229k views
2 votes
Solve the following equation for b. 6b + 2a – 4 = 2b + 3a

Please and thank you!!

2 Answers

4 votes

Answer: b= a+4/4

Step-by-step explanation:just took the test

User Cdrev
by
5.1k points
3 votes

Solve the equation for b, so you need to isolate/get "b" by itself on one side of the equation.

[you can solve this different ways]

6b + 2a - 4 = 2b + 3a First subtract 2b on both sides

4b + 2a - 4 = 3a Next subtract 2a on both sides

4b - 4 = a Then add 4 on both sides

4b = a + 4 Finally divide 4 on both sides


b = (1)/(4)a+1

User VipinYadav
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.